2001
DOI: 10.1152/ajpheart.2001.281.3.h1193
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine linking reduced O2 to arteriolar NO release in intestine is not formed from extracellular ATP

Abstract: We have previously reported that adenosine formed in response to reduced arteriolar and/or tissue PO(2) preserves endothelial nitric oxide (NO) synthesis during sympathetic vasoconstriction in the rat intestine. To more precisely identify the site and mechanism of adenosine formation under these conditions, we tested the hypothesis that ATP released in response to reduced O(2) levels serves as a source of adenosine. Direct application of ATP to the wall of first-order arterioles elicited dose-dependent dilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Although several mechanisms that could mediate this fundamental physiological response have been proposed, none has been universally accepted. For example, it was suggested that arterioles feeding capillary beds in areas of increased O 2 utilization could respond directly to decreased tissue O 2 levels [2,14,19,26] or that a mediator(s) associated with increased O 2 utilization could be released into the venous circulation and diffuse to feed arterioles producing dilation [11,12,27,28]. Although there is experimental data in support of both mechanisms, the results do not fully explain the tight coupling of O 2 supply with demand observed in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Although several mechanisms that could mediate this fundamental physiological response have been proposed, none has been universally accepted. For example, it was suggested that arterioles feeding capillary beds in areas of increased O 2 utilization could respond directly to decreased tissue O 2 levels [2,14,19,26] or that a mediator(s) associated with increased O 2 utilization could be released into the venous circulation and diffuse to feed arterioles producing dilation [11,12,27,28]. Although there is experimental data in support of both mechanisms, the results do not fully explain the tight coupling of O 2 supply with demand observed in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies the animals were anesthetized with pentobarbital ( n = 28, used predominantly in rats and hamsters). Other anesthetics were thiopental [ 33 – 35 ], chloralose [ 36 , 37 ], urethane [ 37 , 38 ], ketamine [ 39 ] or a mixture of droperidol, midazolam and fentanyl [ 40 42 ]. In some studies skinfold windows were applied so that the microcirculation could be observed without anesthesia [ 14 , 43 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the effects reported by the original authors (Table 1 ), raising the P (a) O 2 to hyperoxic levels resulted in vasoconstriction in 91% of the studies. In 7% there was no effect on arteriolar diameter [ 35 , 57 , 58 ] and in one study dilation of second order arterioles was observed [ 43 ]. The median diameter change was − 20% with a range of − 64% to + 6%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation